(untitled) (Comprehensive Journal of Science, 2026)
Transitional contexts have experienceed a rapid expansion In the use of digital platforms, raising questions about their impact on political participation. This study examines whether digital platforms have genuinely enhanced political participation or merely generated new forms of Interaction confined to the digital sphere. Using a descriptive-analytical approach based on a review of relevant lIterature and selected Arab transitional experiencees, the study argues that digital platforms have broadened opportunities for political expression, particularly among youth, and increased awareness of public affairs. However, this expansion does not necessarily translate Into effective institutional participation due to fragile legal frameworks and weak institutional structures. The findings suggest that the impact of digital platforms depends largely on the nature of the political environment, and that dIgital engagement alone cannot replace the need for institutional reform.